Evaluation of Sensory Attributes of Mango Jam (Mangifera indica L.) with Comparison of Sugar Concentration Using Multiple Comparison Method: Evaluasi Atribut Sensoris Selai Mangga (Mangifera indica L.) dengan Perbandingan Konsentrasi Gula Menggunakan Metode Perbandingan Jamak - Aini, Puspita Della; Lesmana, Muhammad Affan; Priyambodo , Hanifah Putri; Sari, Erika Puspita (jurnal makanan tropis dan teknologi agroindustri, 2025)
This study evaluated the effect of sugar concentration on the sensory quality of mango jam, including color, texture, aroma, and taste attributes. Four mango jam samples were tested by 30 panelist using the multiple comparison test method, namely two commercial standard samples (codes A and B) and two experimental samples (code 156 with 40% sugar and code 243 with 15% sugar). The evaluation result were analyzed using a two sample test at a significance level of 5% and 1%. Based on the calculation, the number of responses that A, as well as sample 156 and standard B did not reach the smallest number at the 5% level, indicating the the two experimental samples were not significantly different from their respective standard on all attributes tested.